Prevalence and Risk Factors of Congenital Heart Disease in Patients Admitted in NICU: A Study from Tertiary Care Hospital in Karachi: Congenital Heart Disease in Patients Admitted to the NICU - Zaidi, Farah; Iqbal, Muhammad; Zafar, Farhana; Khan, Lubna; Khalid, Adeel; Lawa, Shivani (Pakistan Journal of Health Sciences, 2025)
Congenital heart disease (CHD) is the most common cause of neonatal morbidity and mortality. The earlier the diagnosis and management, the better the outcome. Several maternal factors predispose to the development of congenital heart disease, including gestational diabetes, pregnancy-induced hypertension, and TORCH infections. Objectives: To determine the frequency and factors associated with CHD in neonates admitted to the Neonatal Intensive Care Unit (NICU) at a tertiary care hospital in Karachi. Methods: A cross-sectional study was conducted from 20 Nov 2024 to Feb 20, 2025, at Ziauddin University Hospital Karachi. Non-probability consecutive sampling included neonates (0-28 days) with confirmed CHD, recurrent respiratory symptoms with a cardiac murmur, or asymptomatic neonates with a cardiac murmur detected on examination. Data were collected regarding maternal risk factors, clinical features, laboratory findings, and neonatal outcomes. Results: A total of 162 neonates were included in the study. The mean maternal age was 30.5 ± 7.7 years. The most common maternal conditions included gestational diabetes (30%) and pregnancy-induced hypertension (37%). Clinical features included tachypnea in 44%, tachycardia in 52%, poor feeding in 48%, and cyanosis in 46%. Common defects were revealed on echocardiography, such as patent ductus arteriosus (23%) and atrial septal defects (19%). The average hospital stay was 16 ± 8.1 days, and the neonatal mortality rate was high. No associations between mortality and maternal factors were established. Conclusions: It was concluded that this study emphasizes a high prevalence of CHD in neonates and its association with maternal risk factors such as gestational diabetes, pregnancy-induced hypertension, and TORCH infections.